RETRACTED: POLITICAL DISCOURSE : A CRITICAL DISCOURSE ANALYSIS OF THE RESISTANCE OF ISLAMOPHOBIC IDEOLOGY IN IMRAN KHAN CONFERENCE TO UNGA - Khushnood Arshad; Sulaiman Ahmad; Sanah Waheed (English Study Program University of Pasir Pengaraian, 2021)
This article has been retracted because it was published in another journal. This article can be found at GLOBAL JOURNAL OF ADVANCED RESEARCH Vol. 7 No 6, December, 2020. http://gjar.org/publishpaper/vol7issue6/d1031r90.pdf